2010
DOI: 10.1111/j.1538-7836.2009.03684.x
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐degrading enzymes inhibit platelet activation in bile duct‐ligated rats

Abstract: Summary. Background: The effect of cholestatic liver disease on primary hemostasis function remains ill-defined. Objectives: To determine platelet function and identify the mechanisms involved in the observed platelet function in cholestatic rats. Methods: Platelet function was studied in a model of 2-week bile duct ligation and compared to that in sham-operated rats with and without a storage pool defect. Results: ADP-induced and collagen-induced platelet aggregation were clearly impaired following bile duct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It has previously been reported that in blood from patients with elevated leucocyte counts, degradation of ADP is accelerated and aggregation in response to ADP is reduced due to increased NTPDase levels (Pulte et al , 2007; Glenn et al , 2008). Moreover, in a rat model of cholestatic liver disease where plasma ectonucleotidase activity is enhanced, reduced aggregation was exhibited in response to ADP and low dose collagen (which is dependent on ADP secretion) (Witters et al , 2010). Conversely, individuals demonstrating reduced ectonucleotidase expression may have more reactive platelets and be more susceptible to thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that in blood from patients with elevated leucocyte counts, degradation of ADP is accelerated and aggregation in response to ADP is reduced due to increased NTPDase levels (Pulte et al , 2007; Glenn et al , 2008). Moreover, in a rat model of cholestatic liver disease where plasma ectonucleotidase activity is enhanced, reduced aggregation was exhibited in response to ADP and low dose collagen (which is dependent on ADP secretion) (Witters et al , 2010). Conversely, individuals demonstrating reduced ectonucleotidase expression may have more reactive platelets and be more susceptible to thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms for altered platelet function in cholestasis are unclear. Several mechanisms have been suggested (Bowen et al, 1988; Pihusch et al, 2002; Atucha et al, 2007; Witters et al, 2010; Tripodi et al, 2011), including an intrinsic change in platelet function, e.g., increased aggregation resulting from altered intracellular calcium (Ca 2+ ) homeostasis or decreased aggregation due to a storage pool deficiency, the effect of a plasmatic factor such as bile acids or bilirubin or because of the effect of release of ADP-degrading enzymes in the circulation. Regarding platelet activation, the necessary increase in cytoplasmic Ca 2+ levels, both by release from internal stores and entry of extracellular Ca 2+ , has been reported to be defective both in experimental models of liver cirrhosis and patients (Bandi et al, 1997; Atucha et al, 2007; Annie-Jeyachristy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibited platelet activation was found by Witters and colleagues who analyzed bile duct ligated rats as well [51]. The authors provided evidence for ADP-degrading enzymes that inhibit platelet activation upon cholestasis in rats.…”
Section: Discussionmentioning
confidence: 73%